2008
DOI: 10.1080/14622200802238852
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and small, dense low-density lipoprotein particles: Cross-sectional study

Abstract: All forms of tobacco cause cardiovascular disease, and tobacco-related disease is a leading cause of death worldwide. Smoking oxidizes low-density lipoprotein (LDL) particles, and oxidized LDL particles are thought to play an early and critical role in atherosclerogenesis. Hyper-low-density lipoproteinemia is one of the risk factors for cardiovascular disease, but small, dense LDL particles have been associated with an increased risk for cardiovascular disease. Small, dense LDL correlates with some cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
3
6
0
1
Order By: Relevance
“…Again, consistent with other studies [28][29][30][31], our baseline findings confirmed an increase in ox-LDL concentration in most of the study population, which indicated that the oxidation of LDL is significantly correlated with the dyslipidemia that characterizes these heavy smokers.…”
Section: Discussionsupporting
confidence: 94%
“…Again, consistent with other studies [28][29][30][31], our baseline findings confirmed an increase in ox-LDL concentration in most of the study population, which indicated that the oxidation of LDL is significantly correlated with the dyslipidemia that characterizes these heavy smokers.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the concentration of blood lipids did not differ significantly between smokers and non-smokers, as confirmed by others [ 24 ]. Interestingly, there are findings on the influence of tobacco smoking on LDL subfraction profile which indicate that smoking is associated with a decrease in the proportion of small, dense LDL particles [ 24 , 25 ]. The densest LDL subfraction was found to contain the lowest CoQ10 levels associated with increased susceptibility to oxidation when compared to the lighter counterparts [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…11,12 No studies, to date, have prospectively evaluated the effects of continued smoking and smoking cessation on lipoproteins in a large, contemporary cohort of current smokers. This is a matter of considerable importance, because smokers in the 21 st century are significantly more overweight than those studied previously.…”
Section: Introductionmentioning
confidence: 99%